The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12693/aphyspola.132.505
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-acrylamido-2-methyl-1-propane sulfonic acid-co-1-vinyl-2-pyrrolidone) Hydrogel and its use in the Removal of Cd(II), Pb(II) and Cu(II)

Abstract: Poly(2-acrylamido-2-methyl-1-propanesulfonic acid-co-1-vinyl-2-pyrrolidone), P(AMPS-co-VP), hydrogel was prepared by free radical cross-linking polymerization method. Prepared hydrogel was used in the competitive removal of Cd(II), Pb(II) and Cu(II) ions from aqueous solution. The characterization of P(AMPS-co-VP) before and after sorption was carried out by the Fourier transform infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy. Atomic absorption spectrometer was used to found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Moreover, the spectrum of AMPSA presents some characteristic peaks: at 3236 cm −1 and corresponding to N-H [ 32 ] stretching vibrations of the amide group, at 3101, 3035, and 1611 cm −1 attributed to H-C=C stretching vibrations of the vinyl group [ 33 , 34 , 35 ] at 1232 and 1076 cm −1 characteristic for the asymmetric and symmetric stretching vibrations of the O=S=O group and additionally at 623 cm −1 assigned to stretching vibrations of the C-S group [ 36 ]. In PS1–PS4, the broad bands in the wavelength range 3600–3100 cm −1 result from the overlapping of the N-H and O-H stretching vibrations [ 37 , 38 ]. Two peaks appeared at positions 2985 and 2938 cm −1 and may be attributed to the aliphatic C-H stretching vibrations [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the spectrum of AMPSA presents some characteristic peaks: at 3236 cm −1 and corresponding to N-H [ 32 ] stretching vibrations of the amide group, at 3101, 3035, and 1611 cm −1 attributed to H-C=C stretching vibrations of the vinyl group [ 33 , 34 , 35 ] at 1232 and 1076 cm −1 characteristic for the asymmetric and symmetric stretching vibrations of the O=S=O group and additionally at 623 cm −1 assigned to stretching vibrations of the C-S group [ 36 ]. In PS1–PS4, the broad bands in the wavelength range 3600–3100 cm −1 result from the overlapping of the N-H and O-H stretching vibrations [ 37 , 38 ]. Two peaks appeared at positions 2985 and 2938 cm −1 and may be attributed to the aliphatic C-H stretching vibrations [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a mass loss of less than 7% at 180 • C. Mass losses were approximately 20, 39 and 68% at 250, 300 and 350 • C, respectively. It was reported that the degradation because of decomposition of the -SO 3 H groups can be seen between 250-300 • C [7,13]. The mass loss from room temperature to 200 • C is due to VP content [4].…”
Section: Thermal Behaviormentioning
confidence: 99%
“…In the previous study, P(AMPS-co-VP) hydrogel was prepared to determine its efficiency in the heavy metal removal. The molar ratio of AMPS to VP was 80/20 and the amount NMBA was 5 mol% of the total monomer concentration [7].…”
Section: Preparation Of P(amps-co-vp) Hydrogelsmentioning
confidence: 99%
“…The removal of heavy metals from water and wastewater is essential because of the numerous adverse effects on human health and the environment [ 1 , 4 , 5 , 6 , 7 ]. Several methods are available such as chemical precipitation [ 8 ], coagulation/flocculation [ 9 ], membrane filtration [ 10 ], ion-exchange [ 11 ], bioremediation [ 12 ] and adsorption [ 13 ].…”
Section: Introductionmentioning
confidence: 99%